Solubility enhancement of statin-based molecules by arginine: thermodynamics, solute-solvent interaction and solid state characterization / Meor Mohd Redzuan Meor Mohd Affandi - Meor Mohd Affandi, Meor Mohd Redzuan (Institute of Graduate Studies, UiTM, 2016)
Categorized as a Biopharmaceutics Classification System (BCS) Class II drugs, statins exhibit low aqueous solubility and bioavailability thus presenting an obstacle and great challenge to formulation researchers. As a consequence, abundant studies are available in regard to the solubility enhancement of statins but very few actually describe this phenomenon in terms of thermodynamics and the solute solvent interaction. The present study aimed to elucidate the solute-solvent and solute-cosolute interactions, solid state characteristics, wetting behaviour, surface energy and thermodynamic parameters that bolstered the solubility of simvastatin (SMV) and atorvastatin (ATV) in the presence of ARG. First, the solubility of SMV and ATV in 0.01, 0.02, 0.04, 0.09, 0.18, 0.36 and 0.73 mol dm-3 arginine (ARG) in water solutions was determined. These solutions were subjected to conductometric, volumetric, viscometric, acoustic and refractometric measurements at temperatures (T) of 298.15, 303.15, 308.15 and 313.15 K. Results indicated that there was a massive increase of SMV and ATV solubility in the presence of ARG as a cosolute. Based on physical characteristics, a strong solute-solvent and solutecosolute interaction has occurred in the SMV-ARG and ATV-ARG binary solution mixture…